Fungsi Ronggeng Amen: Dari Upacara Menjadi Pertunjukan - Tri Reda Julianti Anugrah; Tati Narawati; Ria Sabaria (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This article aims to describe the changes in the function of the ronggeng amen from ceremony to performance. The problem is focused on changes in the form of presentation, accompaniment music, and make-up and clothing used. Data - data collected through observation, interviews, literature, documentation, and analysis qualitatively with descriptive analysis method. Ronggeng amen is one of the traditional arts that developed among the people of Pangandaran Regency. The origin of the Ronggeng Amen art is the development of the Ronggeng Gunung art which was popular in the Pangandaran community. At first, the Ronggeng Gunung art was performed in the fishermen's thanksgiving event which coincided with Friday Keliwon in the month of Muharram. The results of this study obtained data and information regarding the changes in function that occur in ronggeng amen from ceremonies to performances. With the change in function of ronggeng amen, the local community enjoys this art more as a means of entertainment. This study concludes that the existence of ronggeng amen art which functions as a means of entertainment is of benefit to the people of Pangandaran, especially among the Z-gen generation who can regenerate ronggeng amen art well and know more about the art, and this can be a reference for research next in studying the theory of ronggeng amen.